Hydrogen Peroxide from the Oxidative Burst Is Neither Necessary Nor Sufficient for Hypersensitive Cell Death Induction, Phenylalanine Ammonia Lyase Stimulation, Salicylic Acid Accumulation, or Scopoletin Consumption in Cultured Tobacco Cells Treated with Elicitin - Dorey, Stéphan (American Society of Plant Physiologists, 1999)
H(2)O(2) from the oxidative burst, cell death, and defense responses such as the production of phenylalanine ammonia lyase (PAL), salicylic acid (SA), and scopoletin were analyzed in cultured tobacco (Nicotiana tabacum) cells treated with three proteinaceous elicitors: two elicitins (α-megaspermin and β-megaspermin) and one glycoprotein. These three proteins have been isolated from Phytophthora megasperma H20 and have been previously shown to be equally efficient in inducing a hypersensitive response (HR) upon infiltration into tobacco leaves. However, in cultured tobacco cells these elicitors exhibited strikingly different biological activities. β-Megaspermin was the only elicitor that caused cell death and induced a strong, biphasic H(2)O(2) burst. Both elicitins stimulated PAL activity similarly and strongly, while the glycoprotein caused only a slight increase. Only elicitins induced SA accumulation and scopoletin consumption, and β-megaspermin was more efficient. To assess the role of H(2)O(2) in HR cell death and defense response expression in elicitin-treated cells, a gain and loss of function strategy was used. Our results indicated that H(2)O(2) was neither necessary nor sufficient for HR cell death, PAL activation, or SA accumulation, and that extracellular H(2)O(2) was not a direct cause of intracellular scopoletin consumption.